Pendidikan mitigasi bencana likuefaksi dengan model circuit play sebagai upaya pengembangan psikomotorik anak PAUD - Zuama, Shofiyanti Nur (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2024)
Disaster events always bring sadness and suffering that result in damaging and destroying everything. When a disaster occurs, of course the victims who suffer the most are children, so equipping children with knowledge and skills in dealing with disaster situations is important to consider. Liquefaction disaster mitigation education really needs to be attempted and prepared so that children become more responsive and responsive in facing disasters in the future. The purpose of this paper is related to the description and definition of disaster mitigation education, a brief description of liquefaction, then describing the circuit play model, and the recommended psychomotor development for PAUD children. The method used is qualitative research in the form of library research, using several books, related to disaster mitigation education and early childhood education studies; relevant articles, such as knowledge about liquefaction and its impacts, the results of circuit play model research, and other literature as the main objects. The research data is in the form of library data that has been selected, searched, presented and analyzed. The conclusion of this paper is a choice of activities in developing children's psychomotor skills through the circuit play model of liquefaction disaster mitigation. Psychomotor development that appears in children's playing activities with this model is the movement of walking, jumping, hopping, walking on tiptoes, running straight, running zigzag, spinning, crawling in a drum tunnel, and walking on a bottle bridge. The more often children practice with this model, the more alert, flexible, agile their movements become, and make children's fighting power and endurance strong and tough.